The Role of Financial Inclusion in Poverty Reduction: A Production Theory Approach - Astuti, Ismadiyanti Purwaning; Sugiyanto, Franciscus Xaverius; Kurnia, Akhmad Syakir (LifeSciFi, 2022)
This study attempts to analyze the role of financial inclusion in reducing poverty by using a production theory approach. This study used the production function as a function or equation that shows the relationship between the use of input combinations to produce the desired level of output in order to analyze the role of financial inclusion in reducing poverty. The results show that access to financial service products, especially loans, is used as capital input in community production activities. The community uses loans obtained from formal and informal financial institutions to increase their productivity through increased capital. Increased capital will increase output, so income will also increase.